COASTAL DYNAMICS OF SINGKAWANG, WEST KALIMANTAN - Yudi Darlan; Udaya Kamiludin (Marine Geological Institute of Indonesia, 2012)
Morphologically, Singkawang and adjacent area consist of zones beaches, undulating hills, and steep hills. Granitic rocks and alluvium as a based rock of Singkawang coasts. Generally, Singkawang coasts was developed for coastal farms, fishery pond, and beach resorts, where most of these area have been eroded. Geological and physical oceanography condition are the aspects that build the characteristics of Singkawang coast. Human activities also play an important role in managing the equilibrium and dynamics of this coastal region. This research is to determine the dynamics and coastline changes of Singkawang coasts based on the characteristics of the coastal element and sediment. The high erosion was occurred at Semalagi–Cape Bajau. The Cape Bajau - Cape Banjar is relatively stable due to headlands of this coast is characterized by igneous rocks which resistant to the erosion. The Cape Banjar – South Coasts is very intensive erosion coast. Modern shorelines of the Singkawang coast might be as a shallow marine environment which were occurred thousands years ago (pre-Recent). The high of sedimentation process is generated by global sea level change, where was occurred at that time, and might be changed the area become part of the mainland coast of Singkawang. Keywords: coastal dynamics, erosion, sedimentation, Singkawang, West Kalimantan Secara morfologi, Singkawang terdiri atas daerah patai, perbukitan bergelombang, dan perbukitan curam. Batuan granit dan alluvium mengalasi kawasan pesisir Singkawang. Pesisir Singkawang sebagian besar berupa daerah pertanian, tambak ikan, dan tempat wisata yang umumnya merupakan kawasan pantai erosi. Geologi dan oseanografi fisika merupakan aspek yang membentuk karakteristik pantai Singkawang. Aktifitas manusia juga memainkan peranan penting di dalam mengelola kesetimbangan dan dinamika pesisir daerah ini. Penelitian ini untuk mengetahui dinamika dan perubahan garispantai Singkawang berdasarkan karakteristik dan sedimen pantai. Pantai Semalagi – Tanjung Bajau merupakan kawasan pantai erosi kuat. Tanjung Bajau – Tanjung Banjar merupakan kawasan pantai nisbi stabil ujung-ujung TanjungTanjungnya dicirikan oleh batuan beku yang tahan terhadap erosi. Tanjung Banjar – Pantai Selatan merupakan kawasan pantai erosi sangat kuat. Garispantai Singkawang pada saat ribuan tahun sebelum sekarang (pra-Recent) diperkirakan berupa kawasan lingkungan laut dangkal. Karena proses sedimentasi cukup kuat yang ditimbulkan oleh perubahan muka laut global pada saat itu mengubah kawasan tersebut menjadi daratan pantai Singkawang. Kata kunci: Dinamika pantai, erosi, sedimentasi, Singkawang, Kalimantan Barat.